Cell cycle status in AML blast cells from peripheral blood, bone marrow aspirates and trephines and implications for biological studies and treatment. (8th April 2016) - Sellar, Rob S.; Fraser, Laura; Khwaja, Asim; Gale, Rosemary E.; Marafioti, Teresa; Akarca, Ayse; Hubank, Mike; Brooks, Tony; Stoeber, Kai; Williams, Gareth; Linch, David C.
Abstract : Using immunohistochemistry and flow cytometry to define phases of the cell cycle, this study shows that a high proportion of acute myeloid leukaemia (AML) blasts obtained from trephine biopsies are cycling, whereas >95% of peripheral blood‐derived blasts are arrested in G1 . Results obtained from bone marrow aspirates are more similar to those from blood rather than from trephine biopsies. These differences were confirmed by gene expression profiling in a patient with high count AML. This has implications for cell cycle and other biological studies using aspirates rather than trephine biopsies and for the use of cell mobilising agents before chemotherapy.